3x+3=-3x-12

Simple and best practice solution for 3x+3=-3x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+3=-3x-12 equation:


Simplifying
3x + 3 = -3x + -12

Reorder the terms:
3 + 3x = -3x + -12

Reorder the terms:
3 + 3x = -12 + -3x

Solving
3 + 3x = -12 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
3 + 3x + 3x = -12 + -3x + 3x

Combine like terms: 3x + 3x = 6x
3 + 6x = -12 + -3x + 3x

Combine like terms: -3x + 3x = 0
3 + 6x = -12 + 0
3 + 6x = -12

Add '-3' to each side of the equation.
3 + -3 + 6x = -12 + -3

Combine like terms: 3 + -3 = 0
0 + 6x = -12 + -3
6x = -12 + -3

Combine like terms: -12 + -3 = -15
6x = -15

Divide each side by '6'.
x = -2.5

Simplifying
x = -2.5

See similar equations:

| 3p=8p-r | | b+1/6=65 | | 36-7n=1+3(8-6n) | | =(3x-2) | | 62.9296(1.009795073-1.031752943y)+64.9278y=63.54600003 | | 8m-5(m-2)=7 | | -8+5(1+6c)=-27 | | 62.9296(1.009795073-1.031752943y)+64.9278y=63.5460003 | | -582/385=-4/7(n+4/1/10) | | 5/2y+y+5 | | -10(v+2)=-10 | | 3(x-3)+5=25 | | 15m-59= | | -18=-(7-2a)-(9+12) | | -3n-7(2n-1)=45-3(4n+1) | | v+2=-10 | | 4x^7-8x^5= | | 3x-(5x+6)=18 | | 40x+-2=8 | | 179=-3x+7(-3x+5) | | 3-4(2-5x)=51 | | 80x^2+68x+12= | | (256x^12y^16)^1/4 | | 3j+34=12 | | g-3.75=49.75 | | 10x-3(2x+5)=13 | | 58p/4=20 | | 55=-7v+6 | | -123x+16-27x+297=19x-(74+120) | | 62.9296(1.009795073-1.031752943y)+64.9278y=63.546 | | 2x+4-2.8=4.5 | | b/2-7=-17 |

Equations solver categories